Radiofrequency ablation of stage IA non–small cell lung cancer in medically inoperable patients: Results from the American College of Surgeons Oncology Group Z4033 (Alliance) trial. Issue 19 (19th June 2015) - Dupuy, Damian E.; Fernando, Hiran C.; Hillman, Shauna; Ng, Thomas; Tan, Angelina D.; Sharma, Amita; Rilling, William S.; Hong, Kelvin; Putnam, Joe B.
<x xml:space="preserve">Abstract</x> BACKGROUND This study evaluated the 2‐year overall survival rate, adverse event rate, local control rate, and impact on pulmonary function tests for medically inoperable patients with stage IA non–small cell lung cancer (NSCLC) undergoing computed tomography (CT)–guided radiofrequency ablation (RFA) in a prospective, multicenter trial. METHODS Fifty‐four patients (25 men and 29 women) with a median age of 76 years (range, 60‐89 years) were enrolled from 16 US centers; 51 patients were eligible for evaluation (they had biopsy‐proven stage IA NSCLC and were deemed medically inoperable by a board‐certified thoracic surgeon). Pulmonary function tests were performed within the 60 days before RFA and 3 and 24 months after RFA. Adverse events were recorded and categorized. Patients were followed with CT and fludeoxyglucose positron emission tomography. Local control rate and recurrence patterns were analyzed. RESULTS The overall survival rate was 86.3% at 1 year and 69.8% at 2 years. The local tumor recurrence–free rate was 68.9% at 1 year and 59.8% at 2 years and was worse for tumors > 2 cm. In the 19 patients with local recurrence, 11 were re‐treated with RFA, 9 underwent radiation, and 3 underwent chemotherapy. There were 21 grade 3 adverse events, 2 grade 4 adverse events, and 1 grade 5 adverse event in 12 patients within the first 90 days after RFA. None of the grade 4 or 5 adverse events were attributable to RFA. There was no significant change in the forced expiratory volume in the first second of expiration or the diffusing capacity of lung for carbon monoxide after RFA. A tumor size less than 2.0 cm and a performance status of 0 or 1 were associated with statistically significant improved survival of 83% and 78%, respectively, at 2 years. CONCLUSIONS RFA is a single, minimally invasive procedure that is well tolerated in medically inoperable patients, does not adversely affect pulmonary function tests, and provides a 2‐year overall survival rate that is comparable to the rate reported after stereotactic body radiotherapy in similar patients. Cancer 2015;121:3435–43. © 2015 American Cancer Society.